Neutron Radiation Dose Measurements in a Scanning Proton Therapy Room: Can Parents Remain Near Their Children During Treatment? - Mares, Vladimir; Farah, Jad; De Saint-Hubert, Marijke; Domański, Szymon; Domingo, Carles; Dommert, Martin; Kłodowska, Magdalena; Krzempek, Katarzyna; Kuć, Michał; Martínez-Rovira, Immaculada; Michaś, Edyta; Mojżeszek, Natalia; et al. (Frontiers in Oncology, 2022)
Purpose: To characterize the neutron radiation field inside a scanning proton therapy treatment room including the impact of different pediatric patient sizes. Materials and methods: Working Group 9 of the European Radiation Dosimetry Group (EURADOS) has performed a comprehensive measurement campaign to measure neutron ambient dose equivalent, H*(10), at eight different positions around 1-year, 5-year and 10-year old pediatric anthropomorphic phantoms irradiated with a simulated brain tumour treatment. Several active detector systems were used. Results: The neutron dose mapping within the gantry room showed that H*(10) values significantly decreased with distance and angular deviation with respect to the beam axis. A maximum value of about 19.5 µSv/Gy was measured along the beam axis at 1 m from the isocenter for a 10-year old pediatric phantom at 270° gantry angle. A minimum value of 0.1 µSv/Gy was measured at distance of 2.25 m perpendicular to the beam axis for a 1-year old pediatric phantom at 140° gantry angle. The H*(10) dependence on the size of pediatric patient was observed. At 270° gantry position, the measured neutron H*(10) values for 10-year old pediatric phantom were up to 20% higher than those measured for the 5-year and up to 410% higher than for the 1-year old phantom, respectively. Conclusions: It is shown that the neutron ambient dose equivalent H*(10) significantly decreases with distance and angle with respect to the beam axis. It is reported that the total neutron exposure of a person staying at a position perpendicular to the beam axis at a distance greater than 2 m from the isocentre remains much below the dose limit of 1 mSv per year for general public (recommended by the International Commission on Radiological Protection) during the whole treatment course with a target dose up to 60 Gy. This comprehensive analysis is key for general neutron shielding issues, for example the safe operation of anaesthetic equipment. However, it also enables the evaluation of whether it is safe for parents to remain near their children during treatment to bring them comfort. Currently, radiation protection protocols make occupancy of the treatment room during beam delivery prohibitive.